Desarrollo de las habilidades sociales de los niños con baja visión, sus padres y maestros. - Salazar Jácome, Rocio del Consuelo (2014)
This research work deals with social skills developed by students of the Institute of Special Education North having associated with its moderate or severe intellectual disabilities, Down syndrome, low vision; how these influence their behavior and adaptation to the environment in which they operate. The qualitative research was aimed at describing the development of their social skills, evaluate and analyze the level of development of these, the needs of parents in relation to the acquisition of these skills and knowledge that teachers have the same .